BIOSORPSI ION Cr(III) PADA RUMPUT LAUT Eucheuma Spinosum TERAKTIVASI ASAM SULFAT - I W. Sudiarta (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Biosorption of chromium(III) ion on sulfuric acid activated algae (Eucheuma spinosum) biosorbent havebeen studied in this research. The studies included determination of optimum ratio of sulphuric acid to biosorbentalgae, biosorbent acidity, isoterm and biosorption capacity, and interaction mechanisms of Cr(III) on biosorbent. Themechanisms interaction of Cr(III) on biosorbent can be determinted from the sequential desorption of Cr(III) usingH2O, 1M HCl and 0.05M Na2EDTA.The result showed that the optimum ratio of sulphuric acid to biosorbent was 1.5 mmol/g. It was also foundthat the total acidity of acid-activated and untreated algae biosorbent were 8.56±0.21 and 2.59± 0.28 mmol/grespectively. The biosorption capacity of activated biosorbent toward Cr(III) was 72.33 mg/g while the capacity ofuntreated biosorbent was 57.32 mg/g. The interaction mechanisms of Cr(III) with biosorbent were found to bemainly through the ionic interaction, while the interaction through hydrogen bonding, van der Walls, andcomplexation were found to be relative us low.